Evidence-based local planning and budgeting using CBMS - Celia M. Reyes; Anna Rita P. Vargas; Arkin A. Arboneda (Philippine Institute for Development Studies (PIDS), 2021)
The Community-Based Monitoring System (CBMS), which is an organized technology-based system of collecting, processing and validating local-level data based on a census of households in the locality, was institutionalized by virtue of Republic Act No. 11315 in April 2019. This paper aims to illustrate uses of the CBMS in relation to the planning process of local government units. The study finds that since the CBMS provides disaggregated local-level data, local planners can use the CBMS to better identify and target vulnerable members of the society. Regular conduct of CBMS also offers the possibility of generating panel data, which can help monitor the impact of policies and programs on vulnerable households in the long run. Moreover, geotagging of households also support local officials in locating those at risk from natural hazards.
Keywords: 330; Local planning process; Community-Based Monitoring System; Comprehensive Development Plan; local government units; RA 7160